Fraturas em idosos por quedas acidentais no domicílio - Sato, Lílian Aparecida Venancio (2009)
People with 60 years of age or older can have their autonomy and their independence changed because of the consequences of falls, among other causes, considered as public health problems, because they lead to limiting effects for them (LAMBERT et al., 1988). The justification of this study was due to the number of injuries caused by accidental falls, as the population gets older (LACH, 2002). The aim of this study was to identify the elderly who have suffered fractures in accidental falls in their homes, describe their profile and show the causes and results of these accidents. The study was conducted in a university hospital in a large public group, located in Londrina PR. The subjects were patients aged less than 60 years who came to this hospital due to fractures resulting from accidental falls at home from December 2007 to June 2008. The form used consisted of 14 open and closed questions containing data related to the fall of the elderly. This way, we got to the following conclusions: falls are a real event in the life of the elderly; they affected mainly women, a total of 58.1%. The elderly who have suffered more falls were those aged 66 to 70 years (48.6%). The places where there were most falls were in the living room and kitchen, making a total of 66.2%. The fractures which were most found in this study were of the femur (33.8%). Related to what the elderly was doing during the fall, the majority (62.2%) said that they were walking, and, according to the literature, most of the falls in the elderly is associated with ADLs. Among the drugs used by seniors, were the antihypertensive and hypoglycemic, according to several studies that approach the medication of the elderly. We also noticed that a significant number of older people made use of benzodiazepines, a medication related to the occurrence of falls in older people, according to the literature. Related to the use of alcohol, this study showed no significant numbers to compare with the literature, only four of the elderly made continuous use of drinks. Concerning recurrent falls in the last three months, most patients did not have them, thus, in accord with the literature and showing that most patients have at least one fall during the year. We observed that most elderly respondents made use of glasses or lenses, showing that there is diminished eyesight acuity, being one of the triggering factors of falls, according to the literature. Most elderly people have said that they have home environmental risk factors, such as stairs and ramps with sliding floor with and without support, agreeing with the literature and indicating the possible extrinsic factors responsible for a large number of falls. In this study, we further noticed that 56.8% of the elderly had feet problems or used inappropriate footwear. According to the literature studied, that is another factor in propensity to falls. The main carers of the elderly, found in the questionnaires, are the wife (husband) and children (son or daughter), as it is shown in several studies read for this work.